El consumo de alcohol y su incidencia en la violencia intrafamiliar en la comunidad indígena wayuu (2021)
During the development of this research, the subject of alcohol consumption will be worked on. and the impact it has on domestic violence in the Wayuu community, the objectives of this analysis is to document the incidence that alcohol consumption has on violence intrafamily in the Wayuu indigenous community, in this way sources were reviewed Documentaries that allow describing the incidence of alcohol consumption, the characteristics associated with consumption and the relationship with domestic violence; methodologically, it is considered a qualitative study, with a review design documentary, which by means of a matrix the information will be collected and from this summaries of the documents will be made and the analysis can be carried out; taking into account each of the contributions made by the authors of the different documents, attending to aspects of consumption, domestic violence, and community